Essays on the simulation-based estimation of dynamic discrete choice models - Waltmann, B (2021)
A common complaint about structural work in applied microeconomics is that its methods are insufficiently transparent and its findings are not robust enough (see e.g. Angrist and Pischke, 2010). This critique seems especially on target in the context of complex dynamic models with large numbers of parameters, which are the subject of this thesis. In this literature, the important consequences of seemingly technical assumptions are often opaque even to the researchers themselves. Any two researchers may make different choices about how to specify and estimate a model, leading to different results.